Analisis Dampak Alih Fungsi Lahan Pertanian Terhadap Kesejahteraan Petani Dalam Perspektif Maqasid Al-Syariah - Rahmat Firdaus; Rizal Rizal; Febria Rahim; Muhammad Tsaqif Aliva (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2026)
The conversion of paddy fields into fish farming ponds in Tanjung Raya District, Agam Regency, has increased significantly in recent years, generating economic, social, and agricultural sustainability implications. Previous studies have predominantly examined this phenomenon from economic and environmental perspectives, while research integrating the Maqasid al-Shariah framework remains limited. This study aims to analyze the impact of agricultural land conversion on farmers' welfare from the perspective of Maqasid al-Shariah. This research employed a qualitative field-study approach. Data were collected through in-depth interviews, observations, and documentation involving 15 purposively selected informants, including farmers who had converted their agricultural land, community leaders, and other relevant stakeholders. The data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings reveal that land conversion is driven by two primary factors. First, economic considerations, as fish farming offers higher income potential than rice cultivation. Second, natural conditions, particularly the availability of abundant and sustainable water resources that support aquaculture activities. The positive impacts experienced by farmers include increased household income, greater efficiency in labor and time utilization, and the emergence of new business opportunities. From the perspective of Maqasid al-Shariah, these outcomes reflect the realization of hifz al-mal (protection of wealth) and hifz al-nafs (protection of life). However, land conversion also generates negative consequences, including the reduction of productive agricultural land, declining rice production, fewer employment opportunities for agricultural laborers, and the erosion of social values such as mutual cooperation and community solidarity. Therefore, sustainable land management policies are required to maintain a balance between economic welfare, food security, and public welfare (maslahah).